Clinical and biochemical profile of thyroid disorders in pediatric patients: a cross-sectional study - Sadiya, Salma; Alam, Azmeri; Monowara, Mahmuda; Rahman, Sultana Nadira; Saha, Rinky Rani; Rana, M. Masud; Sheikh, Rafsan (International Journal of Contemporary Pediatrics, 2025)
Background: Thyroid disorders in children can significantly impact growth, development, and metabolic functions. Early identification and appropriate management are essential to prevent long-term complications. This study aimed to assess the clinical presentations and biochemical profiles of thyroid dysfunction among pediatric patients in a tertiary care setting in Bangladesh. Methods: A cross-sectional observational study was conducted at the Department of Biochemistry and Molecular Biology and at the Department of Pediatric Endocrinology and Metabolic Disorder, Bangladesh Shishu hospital and institute, Dhaka, from June 2024 to December 2024. A total of 103 children aged 0 to 18 years, presenting with suspected thyroid dysfunction, were enrolled. Clinical features and thyroid hormone levels free triiodothyronine (FT3) and free thyroxine (FT4)-and thyroid stimulating hormone (TSH) were recorded and analyzed using SPSS version 25. Results: Among 103 patients, 67 (65%) were male. Normal thyroid function was observed in 64 (62.1%) cases. Hypothyroidism was the most common thyroid disorder (n=21; 20.4%), comprising 7.8% with primary and 12.6% with subclinical hypothyroidism. Hyperthyroidism affected 14.5%, while 2.9% had central hypothyroidism. Primary hypothyroidism showed low FT3 (1.9±0.4 ng/dl), FT4 (0.7±0.2 pg/ml), and high TSH (13.8±4.1 µIU/mL), whereas hyperthyroidism showed elevated FT3 and FT4 with suppressed TSH. Central hypothyroidism presented with low FT4 and TSH. Common clinical features included neonatal jaundice (28.2%), constipation (21.4%), developmental delay (17.5%), and failure to thrive (15.5%). Conclusions: Thyroid disorders in pediatric patients present with diverse clinical symptoms and hormone profiles. Routine screening in symptomatic children is essential for timely diagnosis and intervention, especially in resource-limited settings.